Closing of a Running Mine and Suggesting a New Approach of Winning of Otherwise-Left Unextracted Coal Reserves - Singh, Satyendra K.; Singh, Raghavendra; Singh, Awanindra P.; Agrawal, Harshit (Journal of Mines, Metals and Fuels, 2022)
In the workable Rayatwari seam of CRC colliery, WCL, having thickness of about 17m, 2nd lift depillaring was reportedly completed in the year 2001. Till 2009, no activity was undertaken as the areas were known cases of poor stowing and in some areas 'no stowing' was done due to many technical and some non-technical reasons. At some worst places, the roof collapses exposed even the sandstone roof. The study, with an aim to find a solution and as described briefly in this paper, has assessed the associated risks, overlying roof strata and the general regional stability of the mine and also reasons for those. The low block safety factor contours in simulated models of the mine suggested the expected high rock load to be supported that was found unpractical to execute. Moreover, the re-supporting exercises would call for additional risk to men and machine and might not be feasible technically as well as economically. To provide an alternative to the mine life and also to provide ingress and egress to the dip-side coal reserves, it was recommended to drive at least two sets of galleries in coal, suitably located keeping the sandstone or the competent coal (if weak shale/weathered sandstone is encountered) in roof of these galleries. Subsequently depillaring of the developed coal reserves, but hitherto located inaccessibly at dip-side of main dip at the moment, may then be taken up. The Indian inspectorate supported the recommendations by CSIR-CIMFR and the mine has recently started implementing the same.